The Maintenance Algorithm of Patients with Myopia and the Risk of Asthenopia after Keratorefractive Surgery - I. A. Mushkova; N. V. Maychuk; E. Yu. Markova; L. T. Shamsetdinova (Oftalʹmologiâ)
Purpose. To develop a step-by-step algorithm for managing patients with myopia and the risk of developing asthenopia after keratorefractive surgery (KRS) to optimize the work of the ophthalmologist and increase patient  satisfaction with the results of the operation.Materials and methods. 66 patients (132 eyes) with moderate to high myopia were examined. The special  research methods needed to create an algorithm for managing patients with myopia and the risk of developing asthenopia after corneal surgery were the study of binocular vision, fusional reserves, and a cover/uncover test to identify heterophoria and heterotropy. Results. Based on the identified of PA predictors development and the developed course of functional treatment of accommodation and binocular function disorders in patients with moderate and high myopia, after CLRS, a step-by-step algorithm was developed for managing patients with myopia and the risk of developing PA. Conclusion. Optimization of the ophthalmologist’s work and an increase the patient’s satisfaction with theresults of excimer laser corneal surgery.